PENGARUH KOMUNIKASI WORD OF MOUTH TERHADAP BRAND AWARENESS KONSUMEN E-COMMERCE SORABEL - Tiara Myas Utami; Diajeng Herika Hermanu (Jurusan Ilmu Komunikasi Universitas Andalas, 2020)
The purpose of this research was to determine the effect of Word of Mouth on Brand Awareness of Consumer e - Commerce Sorabel. The data was collected by distributing questionnaires to 400 female respondents aged 16 – 45 years old who lived in DKI Jakarta. The research used quantitative explanative method with simple linear regression. The research’s results is to inform which is Word of Mouth has a theoretical indicator of positive things, promote, encourage and recommend, besides that the Word of Mouth has a partial influence on Brand Awareness.